ANALISIS PEMASARAN PADI SAWAH TADAH HUJAN DI KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Nurhazanah Nurhazanah; Evy Maharani; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Agricultural marketing is a process of the flow of commodities accompanied by the transfer of property and creation for the time, place and use of forms by marketing institutions by implementing one or more marketing functions.This study aims to analyze the marketing of rainfed lowland rice in Siak Kecil Subdistrict. This research was conducted in Siak KecilSubdistrictofBengkalis Regency using survey method. The technique of taking respondents is done by purposive sampling. The population in this research is rice farmer with 42 farmers. The results showed that the selling price of rice by tauke milling to the final consumer and the selling price given tauke to traders is quite high.This is due to the processing by incurring machine operating costs and labor costs. Marketing margins on channel I and II amounted to 11.11 percent involving farmers, tauke grinders and retailers. The high margin of marketing is due to retailers selling rice to Bandar sungai market located in Siak Kecil Subdistrict. Keywords: agricultural,rice, marketing,production